IMAGE GENERATING DEVICE, IMAGE GENERATING METHOD, RECORDING MEDIUM GENERATING METHOD, LEARNING MODEL GENERATING DEVICE, LEARNING MODEL GENERATING METHOD, LEARNING MODEL, DATA PROCESSING DEVICE, DATA PROCESSING METHOD, INFERRING METHOD, ELECTRONIC INSTRUMENT, GENERATING METHOD, PROGRAM, AND NON-TRANSITORY COMPUTER-READABLE MEDIUM - SHINMI Yusuke; HOSAKA Hajime; HATA Ryuhei; ANDO Yoshiki; NOMURA Yoshikuni; MORIYAMA Yutaka (2021)
[Problem] To acquire training data using computer graphics. [Solution] This image generating method includes: acquiring a CG model or an artificial image generated on the basis of the CG model; and using a processor to subject the CG model or the artificial image to manipulation processing, to generate metadata of a manipulated image or the artificial image, for use in AI learning employed for an image acquired using a sensor. Le problème décrit par la présente invention est d'acquérir des données d'apprentissage à l'aide d'infographies. À cet effet, ce procédé de génération d'image comprend : l'acquisition d'un modèle CG ou d'une image artificielle générée sur la base du modèle CG; et l'utilisation d'un processeur pour soumettre le modèle CG ou l'image artificielle à un traitement de manipulation, pour générer des métadonnées d'une image manipulée ou de l'image artificielle, pour une utilisation dans l'apprentissage IA utilisé pour une image acquise à l'aide d'un capteur. ［課題］コンピュータグラフィックスを用いて訓練データを取得する。 ［解決手段］画像生成方法は、CGモデル又は前記CGモデルに基づいて生成された人工画像を取得することと、プロセッサにより、前記CGモデル又は前記人工画像に対して加工処理を施し、センサで取得した画像に対して使用されるAIの学習に用いられる加工画像又は前記人工画像のメタデータを生成することと、を備える。